If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 6 = -3x + -9 Reorder the terms: 6 + -6x = -3x + -9 Reorder the terms: 6 + -6x = -9 + -3x Solving 6 + -6x = -9 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 6 + -6x + 3x = -9 + -3x + 3x Combine like terms: -6x + 3x = -3x 6 + -3x = -9 + -3x + 3x Combine like terms: -3x + 3x = 0 6 + -3x = -9 + 0 6 + -3x = -9 Add '-6' to each side of the equation. 6 + -6 + -3x = -9 + -6 Combine like terms: 6 + -6 = 0 0 + -3x = -9 + -6 -3x = -9 + -6 Combine like terms: -9 + -6 = -15 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| 8x=32x+96 | | 6d+8.7=d+d | | 1.3x+5-1.48x=-.6x-.84+5 | | -6x+6=-3x-8 | | 80x^2+8x=24 | | -6x+3=6x+27 | | 1+5x=-7x+85 | | 4+v=9 | | 9+9x-5=22 | | -5(r+4)= | | 7n+5m+8m+3n= | | x^2-3x-13=6x-21 | | -7x+4-3x=-66 | | 18.8=4w+2.4 | | 8+4x+2x=68 | | 3x+5=7x+18 | | L-7=-4 | | 7-5x+3x=9 | | 1=a | | -402=6(7x-11) | | 180=1x+6x | | 5(x+2)=9(x-26) | | a^2+a=1 | | K-6.4=2.9 | | 448=-8(-10x+4) | | 4x+3(-5x-3)=-64 | | 7(5y-1)=28y | | 20=2+8k+k | | -3+5x-7=20 | | 90=(4x+3) | | 12+2z=5z+27 | | 5x-125=55 |